Hyperthyroidism enhances fetal and placental growth and placental immune cell infiltration - Sánchez, María Belén (2020)
Thyroid dysfunctions cause reproductive disorders as fetal deaths, preterm birth and preeclampsia. Whether thyroid hormones (THs) exert any function in placental immune cells is unknown. Therefore, the aim of our work was to assess the influence of hyperthyroidism on placental immune cells as well as the impact on reproduction in pregnant rats. To this end, 10-12 weeks old Wistar rats were injected with a daily dose of T4 (0.1 or 0.25 mg/kg s.c) to induce hyperthyroidism (hyper) or vehicle in control animals. Rats were mated 8 days after starting T4 treatment and euthanized on day 19 (G19) and 20 (G20) of gestation. Placenta samples were minced to reach single cell suspension. Then, resident placental immune cells (CD45+) were analyzed by flow cytometry and mRNA content of hormone receptors by qPCR. Also, placental and fetus weights and fetus number were measured. Hyper mothers delivered more fetuses compared to controls (p<0.001). The offspring of hyper 0.25 mg/kg mothers weighed more in G19 and G20 (p<0.001). The placentas of the hyper 0.25 mg/kg mothers were heavier than controls only in G19 (p<0.001). Furthermore, we showed a decrease in the expression of progesterone, estrogen and ß2 thyroid receptors in hyper 0.1 mg/kg (p<0.05; p<0.01). On G19, the percentage of leukocytes was significantly higher in both hyper groups (p<0.05 for 0.1 mg/kg; p<0.01 for 0.25 mg/kg). On G20 we showed an increase in leukocyte infiltrate respect to G19 in the control (p<0.001) but not in the hyper group. These results suggest that T4 administration accelerates fetal development and changes the placental sensitivity to ovarian steroids by modulating their receptors expression and advances the increase in placental resident leukocytes. To our knowledge, this is the first report that shows the modulation of resident immune cells by thyroid hormones.